The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5770/cgj.19.233
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Dementia Care in the Community: Identifying Key Quality Assurance Components

Abstract: BackgroundPrimary care-based memory clinics (PCMCs) have been established in several jurisdictions to improve the care for persons with Alzheimer’s disease and related dementias. We sought to identify key quality indicators (QIs), quality improvement mechanisms, and potential barriers and facilitators to the establishment of a quality assurance framework for PCMCs.MethodsWe employed a Delphi approach to obtain consensus from PCMC clinicians and specialist physicians on QIs and quality improvement mechanisms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…( 26 , 27 , 29 ) We have previously shown that close integration of specialists within PCMCs can serve as a means to increase capacity, and this could apply to training related to a standardized physical examination. ( 22 , 30 ) Furthermore, the lack of agreement among respondents regarding which providers are best suited for specific assessment components mirrors our previous results regarding the integration of PCMCs within the broader health system, and the related need for clarity on mutually understood roles among all clinicians across the system. ( 22 )…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…( 26 , 27 , 29 ) We have previously shown that close integration of specialists within PCMCs can serve as a means to increase capacity, and this could apply to training related to a standardized physical examination. ( 22 , 30 ) Furthermore, the lack of agreement among respondents regarding which providers are best suited for specific assessment components mirrors our previous results regarding the integration of PCMCs within the broader health system, and the related need for clarity on mutually understood roles among all clinicians across the system. ( 22 )…”
Section: Discussionsupporting
confidence: 74%
“…( 22 , 30 ) Furthermore, the lack of agreement among respondents regarding which providers are best suited for specific assessment components mirrors our previous results regarding the integration of PCMCs within the broader health system, and the related need for clarity on mutually understood roles among all clinicians across the system. ( 22 )…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There is, however, significant existing evidence that high-volume PCPs achieve their high volume through briefer appointments [9][10][11]. Our use of health administrative data limited the scope of primary care quality indicators for people with dementia we could assess; the relation of high-volume care and quality indicators such as patient or caregiver satisfaction, frequent reassessment of cognitive status and provision of caregiver support [20,48,49] should be studied in subsequent work. Also, our measure of influenza vaccination has only moderate sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Hategan et al (2) examine the associations between emergency department use and homelessness in the geriatric population. Clinical gaps in the in-patient care of geriatric in-patients with heart failure, as perceived by the patient’s caregivers, are systematically examined by Azad et al (3) A careful methodological examination of the Team Standardized Assessment of Clinical Encounter Report (Team StACER) is performed by Dr. Camilla Wong et al ., (4) and Heckman et al (5) examine the key quality assurance components involved in providing good community dementia care.…”
mentioning
confidence: 99%